Dietary behaviors and physical fitness among Chinese adolescents aged 13–16 years: a comparative study on breakfast, eggs, dairy, and sugar-sweetened beverages by urban–rural location and sex - Li, Youjia; He, Shaokai; Wang, Liangsen; Ma, Wenyue; Zhu, Wenfei; Hou, Ying; Sun, Yuliang (Frontiers in Nutrition, 2026)
BackgroundThis study aims to investigate the associations between four dietary behaviors and physical fitness among Chinese adolescents aged 13–16, with particular attention to urban–rural and sex-related differences.MethodsThe data were obtained from the Chinese National Survey on Students’ Constitution and Health (CNSSCH). The analysis included 43,194 participants aged 13–16 from urban and rural China. Multivariable linear regression analyses were used to examine associations between dietary and physical fitness, adjusting for physical activity, sleep duration, and sedentary time.ResultsMore frequent consumption of breakfast, eggs, and dairy products was linked to better physical fitness outcomes in all groups. Higher intake of sugar-sweetened beverages (SSBs) was linked to poorer fitness performance. These relationships were stronger in rural adolescents, especially for strength (β = 0.047, p < 0.001) and endurance (β = −0.063, p < 0.001). The associations were more evident among girls.ConclusionDietary behaviors were related to physical fitness in adolescents aged 13–16. The relationships were stronger in rural areas than in urban areas. Regular intake of breakfast, eggs, and dairy products was linked to better strength, speed, and endurance. Overall, higher consumption of breakfast, eggs, and milk, and reduced intake of SSBs were associated with modestly better physical fitness outcomes among adolescents.